(Re)inhaling the joy of life : interjection and expressiveness - Bobińska, Anna (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
A particular nature of the interjection is that it refers principally to the emotional dimension of discourse. As a purely expressive phenomenon, it embodies both verbal construction and expression of emotional states in perfect fashion. It can also be related to the enunciative subjectivity. Therefore, in this paper, we attempt to examine the interrelation between emotion and interjection in order to determine the role that this grammatical category plays in a discourse based on the affective component and, more specifically, in the expression of joy.We focus mainly on the functional and pragmatic values of interjections. On the one hand, this approach will allow us to make some remarks on the importance of context in decoding the semantic content of interjections; on the other, it will enable us to reflect on the effects that the use of ejaculatory utterances can produce. Our study is based on the written language corpus derived from the contemporary French comic strips and webcomics published after the year 2000.